2015
DOI: 10.14740/jocmr2141w
|View full text |Cite
|
Sign up to set email alerts
|

Does the Removal of Spinal Implants Reduce Back Pain?

Abstract: BackgroundThe importance of the removal of spinal implants is known in the presence of infection. However, the benefits and/or risks of the removal of spinal implant for the management of back pain are not clear.MethodsIn this retrospective study, we aimed to evaluate the beneficial effects of the removal of spinal implants for back pain. Study included 25 patients with thoracolumbar instrumentation.ResultsSeventeen (68%) of them were male. Indications for spinal instrumentation were vertebra fracture (n = 9),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…After removing their implants, the mean visual analog scale score was decreased from 8.08 to 3.36 points, but ve (20%) patients (including all four recurrent LDH cases) did not report a reduction in pain. Meanwhile, no patient reported complete relief from pain (10) in an investigation of 57 patients who underwent implant removal after fusion and xation because of pain and discomfort; the initial diagnoses in this study were fracture (40%) and degenerative spine disease (58%). In a survey conducted from six to 24 months after surgery, 36 (61%) patients stated that they had experienced some bene ts of the operation, but only seven (12%) of them felt preoperative discomfort had been restored completely; moreover, 36 (63%) patients would undergo the operation again (6).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…After removing their implants, the mean visual analog scale score was decreased from 8.08 to 3.36 points, but ve (20%) patients (including all four recurrent LDH cases) did not report a reduction in pain. Meanwhile, no patient reported complete relief from pain (10) in an investigation of 57 patients who underwent implant removal after fusion and xation because of pain and discomfort; the initial diagnoses in this study were fracture (40%) and degenerative spine disease (58%). In a survey conducted from six to 24 months after surgery, 36 (61%) patients stated that they had experienced some bene ts of the operation, but only seven (12%) of them felt preoperative discomfort had been restored completely; moreover, 36 (63%) patients would undergo the operation again (6).…”
Section: Discussionmentioning
confidence: 60%
“…In practice, whether internal xations located at intervertebral fused segments should be removed has not garnered a consensus among clinicians (9,10) due to a lack of evidence-based clinical investigations. In the present study, we proposed that the removal of internal xations (transpedicular screws and rods, which are inserted into the vertebral pedicle to provide xation) after successful intervertebral fusion would not affect patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is possible that the scapular pain seen in UT patients is as a result of their spinal instrumentation, which has been demonstrated to elicit back pain in previous studies. [28][29][30] Anecdotally, it has been observed that some patients demonstrate an improvement in their scapular pain following instrumentation removal. Indeed, the cause of the scapular pain in UT patients is unclear and could have multiple potential etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, there is anecdotal evidence of reduced scapular pain following instrumentation removal. While studies evaluating implant removal following spine surgery for indications, such as thoracolumbar spine fractures, have shown improved patient quality life and demonstrated adequate safety, [28][29][30]32,33 there remains a paucity of literature surrounding instrumentation removal in ASD patients. Available studies, however, suggest it should be approached with significant caution.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of spinal implants was cautioned by Ak et al, though they showed improved pain scales on VAS in 80% of patients undergoing a second procedure for implant removal [37].…”
Section: Functional Outcomesmentioning
confidence: 99%